WAC Facilitates Mitophagy‐mediated MSC Osteogenesis and New Bone Formation via Protecting PINK1 from Ubiquitination‐Dependent Degradation - Shuai Fan; Jinteng Li; Guan Zheng; Ziyue Ma; Xiaoshuai Peng; Zhongyu Xie; Wenjie Liu; Wenhui Yu; Jiajie Lin; Zepeng Su; Peitao Xu; Peng Wang; et al. (Advanced Science)
Abstract Osteogenic differentiation of mesenchymal stem cells (MSCs) plays a pivotal role in the pathogenesis and treatment of bone‐related conditions such as osteoporosis and bone regeneration. While the WW domain‐containing coiled‐coil adaptor (WAC) protein is primarily associated with transcriptional regulation and autophagy, its involvement in MSC osteogenesis remains unclear. Here, the data reveal that the levels of WAC are diminished in both osteoporosis patients and osteoporosis mouse models. It plays a pivotal function in facilitating MSC osteogenesis and enhancing new bone formation both in vitro and in vivo. Mechanistically, WAC promotes MSC osteogenesis by protecting PINK1, a crucial initiator of mitophagy, from ubiquitination‐dependent degradation thereby activating mitophagy. Interestingly, WAC interacts with the TM domains of PINK1 and prevents the K137 site from ubiquitination modification. The study elucidates the mechanism by which WAC modulates MSC osteogenesis, binds to PINK1 to protect it from ubiquitination, and identifies potential therapeutic targets for osteoporosis and bone defect repair.